The influence of lidocaine and racemic bupivacaine on neuromuscular blockade produced by rocuronium: a study in rat phrenic nerve-diaphragm preparation - Carvalho,Vanessa Henriques (2009)
PURPOSE: To evaluate in vitro lidocaine and racemic bupivacaine effects in neuromuscular transmission and in neuromuscular blockade produced by rocuronium. METHODS: Rats were distributed in 5 groups (n = 5) in agreement with the studied drugs: lidocaine, racemic bupivacaine, rocuronium, separately (Groups I, II, III); rocuronium in preparations exposed to local anesthetics (Groups IV, V). The concentrations used were: 20 µg/mL, 5 µg/mL and 4 µg/mL, for lidocaine, bupivacaine and rocuronium, respectively. It was evaluated: 1) amplitude of diaphragm muscle response to indirect stimulation, before and 60 minutes after separately addition of lidocaine, racemic bupivacaine and rocuronium and the association of local anesthetics - rocuronium; 2) membrane potentials (MP) and miniature end-plate potentials (MEPP). RESULTS: Lidocaine and bupivacaine separately didn't alter the amplitude of muscle response and MP. In preparations previously exposed to lidocaine and racemic bupivacaine, the rocuronium blockade was significantly larger (90.10 ± 9.15% and 100%, respectively), in relation to the produced by rocuronium separately (73.12 ± 9.89%). Lidocaine caused an increase in the frequency of MEPP, being followed by blockade; racemic bupivacaine produced decrease being followed by blockade. CONCLUSIONS: Local anesthetics potentiated the blockade caused by rocuronium. The alterations of MEPP identify presynaptic action.